PENERAPAN MODEL MAKE A MATCH BERBANTUAN WEBSITE DALAM PENINGKATAN KETERAMPILAN MENULIS TEKS BERITA - Shafiyah, Najma; Huri, Daman; Nurhasanah, Een (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research describes the application of Make a Match model assisted with website in enhancing writing skills of news text class VII students in SMPN 1 Klari. This research was implemented using a quantitative approach, namely quasi-experiment with pretest posttest nonequivalent control group design. Sample of this research constituted to 82 students. Research data acquire by test techniques that are divided into initial tests and final tests. Data analyzed through descriptive statistics and several tests, including normality, homogeneity, t test, and n-gain score used SPSS version 26. The results proved that there was a fairly high increase for news text writing skills in the experimental class after being given treatment. The increase was proven through the acquisition of an average value from 61,89 to 85,36. Based on this research, the Make a Match model and website have the advantage of increasing activeness and writing skills in learning news texts.